Renal Denervation for Treating Resistant Hypertension: Current Evidence and Future Insights from a Global Perspective - Y. Castro Torres; Richard E. Katholi (International Journal of Hypertension)
Adequate blood pressure control represents an important goal for all physicians due to the complications of hypertension which reduce patients' quality of life. A new interventional strategy to reduce blood pressure has been developed for patients with resistant hypertension. Catheter-based renal denervation has demonstrated excellent results in recent investigations associated with few side effects. With the growing diffusion of this technique worldwide, some medical societies have published consensus statements to guide physicians how to best apply this procedure. Questions remain to be answered such as the long-term durability of renal denervation, the efficacy in patients with other sympathetically mediated diseases, and whether renal denervation would benefit patients with stage 1 hypertension.